Junie B. Jones and a little monkey business - Park, Barbara; Brunkus, Denise (New York : Random House, 1993)
Through a misunderstanding, Junie B. thinks that her new baby brother is really a baby monkey, and her report of this news creates excitement and trouble in her kindergarten class.
"A Stepping Stone book"
"RL: 1.9"--Cover p. [4]
410
Accelerated Reader AR
Keywords: Brothers and sisters -- Juvenile fiction; Kindergarten -- Juvenile fiction; Humorous fiction